PERAN LITERASI KEUANGAN, KREATIVITAS, DAN TOLERANSI RISIKO DALAM MENINGKATKAN OMZET UMKM DIYOGYAKARTA - Prastyatini, Sri Lestari Yuli; Seran, Aprilis Elisabeth (Gorontalo State University, 2026)
This study aims to examine the influence of financial literacy, entrepreneurial creativity, and risk tolerance on sales turnover of Micro, Small, and Medium Enterprises (MSMEs) at Beringharjo Market, Yogyakarta. This quantitative study used a questionnaire distributed to MSME owners in the market as a data collection technique. Data analysis was conducted using multiple linear regression to test the effect of each variable on sales turnover. Hypothesis testing was supported by IBM SSPS 25. The results indicate that financial literacy, entrepreneurial creativity, and risk tolerance have a positive and significant influence on MSME turnover. Simultaneously, these three variables explain the variation in sales turnover, while the remaining is influenced by other factors not examined. Based on these findings, the study recommends the importance of improving financial literacy, creativity, and risk tolerance for MSMEs to increase sales turnover. This study also suggests that future research expand the variables and research objects and use more varied data collection methods to obtain a more comprehensive picture.